Care for complex needs children. Issue 12 (2nd December 2021) - Harris, Alexandra Conroy
Abstract : Alexandra Conroy Harris, legal consultant at CoramBAAF, explains how a rise in inherent jurisdiction applications for the deprivation of liberty of children is affecting the care of those with complex needs